A Cross Sectional Study on Pattern of Health Care Seeking Behavior and Out-Of-Pocket Household Expenditure on Curative Medical Care in Rural Central India - Khanam, Najnin; Meshram, Gulab D; Athavale, Arvind V; Goyal, R C; Gupta, Manmohan; Gaidhane, A M (National Journal of Community Medicine, 2013)
Introduction: Effective health care policies and programmes depend on health care seeking behaviour & out-of-pocket household expenditure. Methodology: It is a community based cross-sectional study done in rural area of Seloo block of Wardha district, Maharashtra. Multistage sampling technique was adopted to select study villages. Among the study villages 25% households were selected by systematic sampling method. Sample size was 300 household (unit of study) to study the out-of-pocket household expenditure on curative medical care, in contrast 1319 members (unit of study) of total household were interviewed to know the pattern of health care seeking behavior. Data on socio-demographic profile, morbidity profile, health care seeking behaviors and curative medical care expenditure were collected. Study period was from July 2008 to June 2009. Results: About half (50.13%) of the patients during their illness gave first preference to private practioners. Significant difference between variables (age distribution & education) and health care seeking behavior was noted. More of productive age group participants prefer to go to Private Practitioners 210 (58.33%), Chemist shops 110(82.71%), Tertiary hospitals 40 (83.33%) and Rural hospitals 11(84.62%) than dependents age group. More of secondary schooled personal preferred to go to Chemist shops 81(60.90%), primary health center 38(74.51%) and tertiary hospitals 30 (62.50%) than others. From all the Households average out-of-pocket health care expenditure during last six month was Rs /- 418.72 ± 933.0 SD. Conclusion: Reasons for seeking care in private practitioner to be sorted out so that same or better treatment may be obtained from public health care system with low expenses from competent and trained health care provider.